Information Quality, Performance Measurement, and Security Demand in Rational Expectations Economies - Noe, Thomas H.; Ramamurtie, Buddhavarapu Sailesh (Journal of Finance, 1995)
The relationship between asset demand and information quality in rational expectations economies is analyzed. First we derive a number of new summary descriptive statistics that measure four basic characteristics of investment style: asset selection, market timing, aggressiveness, and specialization. Then we relate these statistics to the divergence between a given investor's information structure and the market average information structure. Finally, we demonstrate that informational differentials can be identified, and consistently estimated, using ordinary least squares, from the time-series of observed asset demand.